Progress in Model Systems of Cystic Fibrosis Mucosal Inflammation to Understand Aberrant Neutrophil Activity - Laucirica, Daniel R.; Garratt, Luke W.; Kicic, Anthony (Frontiers in Immunology, 2020)
In response to recurrent infection in cystic fibrosis (CF), powerful innate immune signals trigger polymorphonuclear neutrophil recruitment into the airway lumen. Exaggerated neutrophil proteolytic activity results in sustained inflammation and scarring of the airways. Consequently, neutrophils and their secretions are reliable clinical biomarkers of lung disease progression. As neutrophils are required to clear infection and yet a direct cause of airway damage, modulating adverse neutrophil activity while preserving their pathogen fighting function remains a key area of CF research. The factors that drive their pathological behavior are still under investigation, especially in early disease when aberrant neutrophil behavior first becomes evident. Here we examine the latest findings of neutrophils in pediatric CF lung disease and proposed mechanisms of their pathogenicity. Highlighted in this review are current and emerging experimental methods for assessing CF mucosal immunity and human neutrophil function in the laboratory.